Analisis Stabilitas Bank Pembiayaan Rakyat Syariah Di Provinsi Banten : Studi Empiris Periode Pasca Pandemi Covid-19 - Fatoni, Ahmad (FEB Universitas Sultan Ageng Tirtayasa, 2023)
This study aims to analyse the stability of Islamic Rural Bank in Banten Province in the post-Covid 19 pandemic period. This research uses a quantitative descriptive approach by taking a sample of 8 BPRS in Banten Province. The data in this study are semester data, namely June 2020 to June 2022. The stability measures used in this study are Z-Score and Non Performing Financing. The results found that the average Z-Score value of BPRS Banten Province was 4.67. BPRS Cilegon Mandiri has the highest average Z-Score value than other BPRS. However, BPRS Cilegon Mandiri has the highest average value of Non Performing Financing during the observation period.